141k views
4 votes
Solve for x
3(3x-8)-5(3x-8)=(4x-16)-6(x-2)

1 Answer

1 vote

Answer:

the answer should be 5

Explanation:

Remove parentheses.

3(3x-8)-5(3x-8)=4x-16-6(x-2)3(3x−8)−5(3x−8)=4x−16−6(x−2)

2 Simplify 3(3x-8)-5(3x-8)3(3x−8)−5(3x−8) to -2(3x-8)−2(3x−8).

-2(3x-8)=4x-16-6(x-2)−2(3x−8)=4x−16−6(x−2)

3 Expand.

-6x+16=4x-16-6x+12−6x+16=4x−16−6x+12

4 Simplify 4x-16-6x+124x−16−6x+12 to -2x-4−2x−4.

-6x+16=-2x-4−6x+16=−2x−4

5 Add 6x6x to both sides.

16=-2x-4+6x16=−2x−4+6x

6 Simplify -2x-4+6x−2x−4+6x to 4x-44x−4.

16=4x-416=4x−4

7 Add 44 to both sides.

16+4=4x16+4=4x

8 Simplify 16+416+4 to 2020.

20=4x20=4x

9 Divide both sides by 44.

\frac{20}{4}=x

​4

​20

​​ =x

10 Simplify \frac{20}{4}

​4

​20

​​ to 55.

5=x5=x

11 Switch sides.

x=5x=5

User Jason Sperske
by
5.5k points